Identifikasi Kondisi Kualitas Pelayanan Air Bersih Berdasarkan Persepsi Masyarakat Di Kelurahan Baru Tengah, Kota Balikpapan - Sinaga, Mutiara; Pratama , Maryo Inri; Syafitri , Elin Diyah; Kadri, Mohtana Kharisma (COMPACT: Spatial Development Journal, 2024)
The clean water distribution in Baru Tengah Subdistrict is managed by PERUMDA Tirta Manuntung Kota Balikpapan. Currently, the clean water service provided still causes complaints from the community, particularly regarding the continuity of water supply, which is not continuous for 24 hours. The inadequate clean water service results in the community's needs for clean water not being met in terms of quantity, quality, and continuity. The aim of this research is to identify the quality of clean water service received by the community. The data used in this research is primary data obtained from questionnaires distributed to PDAM customers in Baru Tengah Subdistrict. This study employs a quantitative method with a scoring analysis technique. Based on the analysis results, it is known that the quality of clean water service, according to the community's perception in Baru Tengah Subdistrict, has an average score indicating poor service quality.. Keywords : Clean Water, Continuity, Quality, Quantity